2018
DOI: 10.1371/journal.pone.0189940
|View full text |Cite
|
Sign up to set email alerts
|

What influences where they seek care? Caregivers’ preferences for under-five child healthcare services in urban slums of Malawi: A discrete choice experiment

Abstract: Access to and utilisation of quality healthcare promotes positive child health outcomes. However, to be optimally utilised, the healthcare system needs to be responsive to the expectations of the population it serves. Health systems in many sub-Saharan African countries, including Malawi, have historically focused on promoting access to health services by the rural poor. However, in the context of increasing urbanisation and consequent proliferation of urban slums, promoting health of children under five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 34 publications
(56 reference statements)
4
26
0
2
Order By: Relevance
“…It is probable that the fact that a significant majority of caregivers utilized public health facilities which provide free services at the point of use in Malawi, entailed that household wealth may not have had a significant effect in care-seeking dynamics. Relatedly, our discrete choice experiment study responded to by a subset of participants used in this study revealed that cost of healthcare negatively influenced the choice of a health facility in the event of childhood illness, effectively intimating caregivers' aversion with cost of healthcare [51].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is probable that the fact that a significant majority of caregivers utilized public health facilities which provide free services at the point of use in Malawi, entailed that household wealth may not have had a significant effect in care-seeking dynamics. Relatedly, our discrete choice experiment study responded to by a subset of participants used in this study revealed that cost of healthcare negatively influenced the choice of a health facility in the event of childhood illness, effectively intimating caregivers' aversion with cost of healthcare [51].…”
Section: Discussionmentioning
confidence: 91%
“…In the context of urban health, iCCM in urban slums will reduce congestion at urban health centres effectively lessening the burden of long waiting times, and potentially contributing to more time spent on examining children with severe illness at a health facility. Indeed, long waiting times and suboptimal examination of the sick child by health workers have been shown to have negative effect on preference for health facility in the event of childhood illness [51][52][53]. It entails that implementing iCCM may arguably also have a positive effect on overall use of biomedical health services at facility level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there are complaints, they will not refer them to the health office. As a result, their disease tends to be severe and directly requires an inpatient treatment (Gonzales et al, 2017;Lungu et al, 2018). Table 2 shows that age variable also influences the use of puskesmas like the use of inpatient services.…”
Section: Resultsmentioning
confidence: 99%
“…We used 27 alternatives, which is more manageable, using a fractional factorial experimental design [31]. The alternative with the most attributes at the middle level was selected as a comparator and the other 26 alternatives were compared to it, to make the choices easier to understand for respondents [32]. Each choice set consisted of two community health station alternatives, alternative A (the comparator) and alternative B, for which attribute levels were varied systematically.…”
Section: Questionnairementioning
confidence: 99%